Characterization of a silver-incorporated calcium phosphate film by RBS and its antimicrobial effects - Han, I.-H.; Lee, I-S; Song, J-H; Lee, M-H; Park, J-C; Lee, G-H; Sun, X-D; Chung, S-M (IOP PUBLISHING LTD, 2007)
A thin calcium phosphate film was synthesized on both commercially pure Ti and Si wafers by electron beam evaporation of hydroxyapatite as an evaporant with simultaneous Ar ion beam bombardments. Silver was introduced into an ion-beam-assisted deposition of a calcium phosphate thin film for antimicrobial effect. The amount of incorporated silver ions was controlled by immersing calcium-phosphate-coated samples in different AgNO3 concentrations, and Rutherford backscattering spectrometry (RBS) was employed to measure the amounts of substituted silver. The higher concentration of silver in the calcium phosphate film was more effective in reducing the bacteria of Escherichia coli ATCC 8739 and Streptococcus mutans OMZ 65 on contact with respect to controls.
Keywords: HYDROXYAPATITE COATING LAYER; ASSISTED DEPOSITION; IMPLANT; TI